MEASURING MICROFINANCE ACCESS: BUILDING ON EXISTING CROSS-COUNTRY DATA - Patrick Honohan (World Bank Policy Research Working Paper 3606, May 2005, 2005)
Given the acknowledged need for a new effort to expand the set of available data on direct access to financial services, including a focus on access by those at low income, the paper provides a selective review of the diverse sources of data that exist and considers how best to build upon them. It proposes a basic framework within which the analysis of the interesting questions: (i) how does access affect poverty and productivity and (ii) what hinders access, can be considered. The existing and potential contribution of user surveys, both household and business, as well as from surveys of providers and their regulators, and of experts is discussed with an assessment of their relative strengths.